2012
DOI: 10.1158/1538-7445.am2012-1398
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1398: Using zebrafish xenotransplantation to study the role of Y-Box binding protein (YB-1) in the metastasis of Ewing family tumors

Abstract: Sarcomas are malignant cancers of soft tissue or bone predominantly affecting children and adolescents. The most common subtypes are osteosarcoma and Ewing family tumours (EFTs). The most unfavorable prognostic factor is the presence of metastases, which accounts for 9 out of 10 sarcoma cancer deaths. Identifying factors and/or drugs that have an impact on metastatic spread have tremendous potential to affect outcome by reducing disease burden to the primary site, which can be more effectively treated by surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, circulation of leukemic cells and migration of even larger human solid tumor cells, such as sarcoma cells, has been repeatedly demonstrated in zebrafish indicating that passage is possible (Fig. 2A and unpublished data) 68 . Moreover, we have used the nuclear stain, DRAQ5, to confirm that the human cells under observation are intact and not damaged due to injection or passage through the embryo 60 .…”
Section: Advantages and Limitations Of Zebrafish As Hosts For Human Xmentioning
confidence: 63%
See 4 more Smart Citations
“…However, circulation of leukemic cells and migration of even larger human solid tumor cells, such as sarcoma cells, has been repeatedly demonstrated in zebrafish indicating that passage is possible (Fig. 2A and unpublished data) 68 . Moreover, we have used the nuclear stain, DRAQ5, to confirm that the human cells under observation are intact and not damaged due to injection or passage through the embryo 60 .…”
Section: Advantages and Limitations Of Zebrafish As Hosts For Human Xmentioning
confidence: 63%
“…Recruitment of new blood vessels to the vicinity of the xenografted tumor mass can be visualized in real time (Fig. 2B and unpublished data), 68 similar to the more established chicken chorioallantoic membrane (CAM) angiogenesis model, but rivaling this system for more mechanistic studies due to the ease by which the zebrafish host can be genetically modified 89 . In another study, silencing of the two LIM domain kinases LIMK1 and LIMK2 was shown to reduce tumor cell‐induced neovascularization in human pancreatic tumor cell fish xenografts 75 .…”
Section: Evaluation Of Tumor‐induced Angiogenesismentioning
confidence: 86%
See 3 more Smart Citations